Critical vitamin D and iron intakes in infants aged 6–11 months: results from the nationwide German KiESEL study - Burgard, Leonie; Spiegler, Clarissa; Jansen, Sara; Brettschneider, Anna-Kristin; Straßburg, Andrea; Alexy, Ute; Storcksdieck genannt Bonsmann, Stefan; Ensenauer, Regina; Heuer, Thorsten (Frontiers in Nutrition, 2025)
BackgroundNutrient intake during the phase of complementary feeding is pivotal for healthy development, yet current data for European infants are lacking.ObjectiveTo provide latest data on energy and nutrient intake of infants in Germany, to compare these with the Dietary Reference Values (DRVs) of the European Food Safety Authority, and to assess the contribution of vitamin D supplementation and commercial infant foods to nutrient intake.DesignAnalyses are based on weighed food records (3 + 1 day) of 118 infants aged 6–11 months from the representative cross-sectional Children’s Nutrition Survey to Record Food Consumption (KiESEL) conducted in Germany from 2014 to 2017. Energy and nutrient intake was calculated using the German Nutrient Database BLS 3.02, the LEBTAB database, and a supplement database.ResultsMedian energy and protein intakes were above DRVs, while fat intake was below. Dietary vitamin and mineral intakes mostly met or exceeded the DRVs. However, iron intake reached neither the Population Reference Intake nor the Average Requirement. Vitamin D intake from foods was below half the Adequate Intake (AI). When additionally considering vitamin D supplements, administered to 51.7% of infants, the AI was reached. Girls’ iodine intake was below the DRVs. In contrast, the intakes found for retinol equivalents, vitamin K, and vitamin C were about four times the DRVs. Commercial infant foods were key dietary sources for all nutrients for which intakes deviated considerably from DRVs.ConclusionMicronutrient intake, particularly of iron and vitamin D, needs improving in infants aged 6–11 months in Germany. Vitamin D supplementation was a prerequisite for meeting the AI, confirming the necessity for vitamin D supplements in infancy and the promotion of the respective recommendations. The considerable up- and downward deviations from DRVs point to a need for adjusting fortification levels of commercial infant foods in European legislation.